Discoloration of surface sealants by plaque disclosing solution - Şen, Sinan; Erber, Ralf; Şen, Gözde; Deurer, Nadine; Zingler, Sebastian; Lux, Christopher J. (Journal of orofacial orthopedics, 2020)
Surface sealants are widely used as a prevention strategy and are indicated for young patients with insufficient oral hygiene who also need plaque removal by professional tooth cleaning. The aim of this study was to evaluate discoloration of surface sealants by plaque disclosing solutions and to test to what extent this discoloration can be reduced again by professional tooth cleaning.
Gesehen am 12.08.2021